2010 International Conference on Emerging Security Technologies 2010
DOI: 10.1109/est.2010.14
|View full text |Cite
|
Sign up to set email alerts
|

Vision-Based Landing of a Simulated Unmanned Aerial Vehicle with Fast Reinforcement Learning

Abstract: Landing is one of the difficult challenges for an unmanned aerial vehicle (UAV). In this paper, we propose a vision-based landing approach for an autonomous UAV using reinforcement learning (RL). The autonomous UAV learns the landing skill from scratch by interacting with the environment. The reinforcement learning algorithm explored and extended in this study is Least-Squares Policy Iteration (LSPI) to gain a fast learning process and a smooth landing trajectory. The proposed approach has been tested with a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Shaker et al [11] suggested another approach: reinforcement learning. In this approach, the UAV agent learns and adapts its behaviour when required.…”
Section: Category Iii-landing On a Shipmentioning
confidence: 99%
“…Shaker et al [11] suggested another approach: reinforcement learning. In this approach, the UAV agent learns and adapts its behaviour when required.…”
Section: Category Iii-landing On a Shipmentioning
confidence: 99%
“…In 2018, Anwar and Raychowdhury successfully made an unmanned aerial vehicle (UAV) learn to fly in a real environment via end-to-end deep reinforcement learning using monocular images [ 14 ]. Shaker and Smith presented a fast reinforcement learning algorithm for an unmanned aerial vehicle to learn how to automatically land using visual information [ 15 ]. However, most of these works focused on diminutive UAVs and quadcopters, which have simpler structures and are easier to control than complicated and sluggish civil aircraft.…”
Section: Introductionmentioning
confidence: 99%
“…The control of multi-rotor UAVs for autonomous landing on a moving platform has been addressed in several lines of research: Position-Based Visual Servoing (PBVS) [1][2], Image-Based Visual Servoing (IBVS) [3] [4], tethered solutions [5][6] [7] [8], optic flow methods [9][10], high-speed landing with communication between moving platform and the UAV [11], bio-inspired [12] or machine learning based techniques [13] [14]. (i) Position-Based Visual Servoing extracts the position of the target, relative to the UAV and tracks the target in movement.…”
Section: Introductionmentioning
confidence: 99%
“…Non-classical approaches have also been tested, such as the use of artificial neural networks to detect a suitable landing zone [13]. Other learning techniques, such as reinforcement learning, have proven to have a high potential in the autonomous landing field, but were only tested in simulation and with a static platform [14].…”
Section: Introductionmentioning
confidence: 99%